Eksperimentasi Model Pembelajaran Project Based Learning terhadap Prestasi Belajar Mahasiswa: Experimentation of Project-Based Learning Model on Student Learning Achievement - Winata, Rahmat; Friantini, Rizki Nurhana; Sugiharto, Sugiharto; Haryani, Desti (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
In the trigonometry course, the learning achievement achieved by students is not optimal because many students get scores below 70. Researchers find out the causes of these problems, one of which is that the teacher still uses the lecture method and assignments in the learning process. This causes students to only listen to the material without going through the process of trying and finding themselves. The researcher gave the treatment of the Project-Based Learning learning model and conventional learning model so that the purpose of this study was to determine the difference in learning achievement of Mathematics Education Study Program students at Palangka Raya University as prospective teachers who were treated with the Project-Based Learning learning model and conventional learning model. The population of this study was all 1st semester students of the 2024/2025 academic year of the mathematics education study program at Palangka Raya University. Before conducting the analysis using the t-test of two independent samples, the prerequisite test was carried out: normality test with Kolmogorov-Smirnov and homogeneity test with Levene. The results of this study are that there are differences in the learning achievement of students of the Mathematics Education Study Program at Palangka Raya University as prospective teachers who are treated with the Project-Based Learning learning model and the conventional learning model. Furthermore, students in the experimental class using the Project-Based Learning learning model obtained an average achievement of 81.379, while the control class using the conventional learning model obtained an average achievement of 72.008.